Reducing falls in older adults recently discharged from hospital: A systematic review and meta-analysis - Naseri, C.; Haines, T.; Etherton-Beer, C.; McPhail, S.; Morris, M.; Flicker, L.; Netto, J.; Francis-Coad, J.; Lee, D.; Shorr, R.; Hill, Anne-Marie (Oxford University Press, 2018)
Background: older adults are known to have increased falls rates and functional decline following hospital discharge, with substantial economic healthcare costs. This systematic review aimed to synthesise the evidence for effective falls prevention interventions in older adults recently discharged from hospital. Methods: literature searches of six databases of quantitative studies conducted from 1990 to June 2017, reporting falls outcomes of falls prevention interventions for community-dwelling older adults discharged from hospital were included. Study quality was assessed using a standardised JBI critical appraisal tool (MAStARI) and data pooled using Rev-Man Review Manager® Results: sixteen studies (total sample size N = 3,290, from eight countries, mean age 77) comprising 12 interventions met inclusion criteria. We found home hazard modification interventions delivered to those with a previous falls history (1 study), was effective in reducing the number of falls (RR 0.63, 95%CI 0.43, 0.93, Low GRADE evidence). Home exercise interventions (3 studies) significantly increased the proportion of fallers (OR 1.74, 95%CI 1.17, 2.60, Moderate GRADE evidence), and did not significantly reduce falls rate (RR 1.27, 95%CI 0.99, 1.62, Very Low GRADE evidence) or falls injury rate (RR 1.16, 95%CI, 0.83,1.63, Low GRADE evidence). Nutritional supplementation for malnourished older adults (1 study) significantly reduced the proportion of fallers (HR 0.41, 95% CI 0.19, 0.86, Low GRADE evidence). Conclusion: the recommended falls prevention interventions for older adults recently discharged from hospital are to provide home hazard minimisation particularly if they have a recent previous falls history and consider nutritional supplementation if they are malnourished.